2018
DOI: 10.1042/bsr20180503
|View full text |Cite
|
Sign up to set email alerts
|

Piperine functions as a tumor suppressor for human ovarian tumor growth via activation of JNK/p38 MAPK-mediated intrinsic apoptotic pathway

Abstract: Piperine, a kind of natural alkaloid found in the fruit of black ( Linn) and long ( Linn), has shown antitumor activities toward various cancer cell lines. However, the antitumor effects of Piperine on ovarian cancer and the underlying mechanism are not fully elucidated. Our result showed that Piperine reduced the cell viability of A2780 cells in a concentration and time-dependent manner, but has not any effect on normal ovarian cells. Flow cytometric analysis revealed that Piperine suppressed cells proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Also, this compound, together with its analogs demonstrated significant potential against Hela cervix cell line [63]. A recent study showed that piperine (8,16, and 20 µM) inhibited cell viability and caused apoptosis in human ovarian A2780 cells via JNK/p38 MAPK-mediated intrinsic apoptotic pathway [64]. Further analysis on the mechanism of its action demonstrated increased levels of cyt-c from mitochondria and consequently increased caspase (caspase-3 and -9) activities and also decreased phosphorylation of JNK and p38 MAPK following piperine treatment.…”
Section: Cervical and Ovarian Cancermentioning
confidence: 95%
“…Also, this compound, together with its analogs demonstrated significant potential against Hela cervix cell line [63]. A recent study showed that piperine (8,16, and 20 µM) inhibited cell viability and caused apoptosis in human ovarian A2780 cells via JNK/p38 MAPK-mediated intrinsic apoptotic pathway [64]. Further analysis on the mechanism of its action demonstrated increased levels of cyt-c from mitochondria and consequently increased caspase (caspase-3 and -9) activities and also decreased phosphorylation of JNK and p38 MAPK following piperine treatment.…”
Section: Cervical and Ovarian Cancermentioning
confidence: 95%
“…Controlled cell death induced by piperine was shown through the mitochondrial pathway and through the suppression of Akt activation in breast cancer cells. In a recent study, piperine exhibited antitumor property against human ovarian cancer cell line (A2780) [327]. Cell viability was reduced in piperine-treated cancer cells whereas no significant changes were seen in normal cell line.…”
Section: Biological Activities Piper Plantsmentioning
confidence: 99%
“…Piperine exhibits a variety of pharmacological properties, including acting as an anticonvulsant [5], an antioxidant [6], an anti-inflammatory [7], an anti-angiogenic [8], an anti-bacterial, and an anticancer compound. Recent studies have reported that piperine can be cytotoxic to multiple animal and human cancer cells, such as 4T1 mouse breast cancer cells [9], PC-3 human prostate cancer cells [10], and A2780 human ovarian cancer cells [11]. Moreover, PP affects diverse signaling pathways associated with cancer cell growth and survival, including mitogen-activated protein kinase (MAPK), PI3K/Akt, and STAT3 pathways [12,13].…”
Section: Introductionmentioning
confidence: 99%